2007
DOI: 10.1021/nl070900e
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Schottky Barriers and Charge Depletion in Carbon Nanotube Transistors

Abstract: The photovoltage produced by local illumination at the Schottky contacts of carbon nanotube field-effect transistors varies substantially with gate voltage. This is particularly pronounced in ambipolar nanotube transistors where the photovoltage switches sign as the device changes from p-type to n-type. The detailed transition through the insulating state can be recorded by mapping the open-circuit photovoltage as a function of excitation position. These photovoltage images show that the band-bending length ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
151
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 22 publications
6
151
1
Order By: Relevance
“…Although this photoresponsivity is much lower than that of photodetectors based on individual MoS2 flakes, [6,9,39] it is comparable to those based on individual carbon nanotubes [40] or graphene. [41][42][43] In particular, it is also comparable to that of MoS2 nanosheet films fabricated by the Langmuir-Blodggett (LB) method, [16] implying that our inkjet printing processes do not induce obvious performance degradation.…”
Section: Resultsmentioning
confidence: 90%
“…Although this photoresponsivity is much lower than that of photodetectors based on individual MoS2 flakes, [6,9,39] it is comparable to those based on individual carbon nanotubes [40] or graphene. [41][42][43] In particular, it is also comparable to that of MoS2 nanosheet films fabricated by the Langmuir-Blodggett (LB) method, [16] implying that our inkjet printing processes do not induce obvious performance degradation.…”
Section: Resultsmentioning
confidence: 90%
“…34,36,[81][82][83][84][85][86] Even though scanning photocurrent measurements have been used to image the depletion region in CNT-metal contacts, quantitative estimates of the Schottky barrier heights using the photoelectric effect are still lacking. 87 …”
Section: Schottky Barrier Height Measurement Techniquesmentioning
confidence: 99%
“…Therefore, the depletion regions in CNT-metal contacts have been imaged using photocurrent and photovoltage measurements 87 as well as by scanned gate microscopy. 109 In the scanned gate microscopy experiments, it was observed that a biased AFM tip scanned over a CNTFET has a stronger gating effect when the tip is in the vicinity of one of the contacts implying that a barrier is present there.…”
Section: B Imaging Of Depletion Regionmentioning
confidence: 99%
“…These properties make SWNTs an ideal platform for exploring photocurrent generation with SPCM. In early single-walled nanotubes SPCM work the interpretation of photocurrent was mostly based on photovoltaic mechanisms [6,7,8,9,11].The importance of photothermal effects has been suggested in the context of measurements of bulk SWNT films [12,13,14] and very recently, SPCM work on graphene and individual metallic SWNTs has emphasized the importance of photothermal mechanisms in materials with no or small bandgaps [22,26].The question of the role of photothermal mechanisms in larger bandgap semiconducting nanotubes has been studied very recently in double-gated [26] and single-gated [27] suspended carbon nanotube devices.These two studies report contradictory results, leaving the understanding of fundamental mechanisms underlying photocurrent generation in semiconducting nanotubes unclear.Here we report on the study of a suspended semiconducting nanotube device where we show that both photovoltaic and photothermal mechanisms compete in the generation of photocurrent. In particular, we find that the dominant or non-dominant character of one or the other processes is a function of the doping profile and that the magnitude of each contribution is strongly influenced by the band alignment with the metal contacts through the resulting contact resistance.…”
mentioning
confidence: 99%